Towards user centric regulation: exploring the interface between information technology law and human computer interaction - Urquhart, Lachlan (2017)
This thesis investigates the role of technology designers in regulation. Emerging information technologies are complex to regulate. They require new strategies to support traditional approaches. We focus on the use of technology design as a regulatory tool. Whilst this solution has significant conceptual traction, what it means in practice is not clear. Deeper investigation of the role of the design community in regulation is necessary to move these strategies from theory into practice. We structure our analysis by asking: how can we understand the role of designers in regulation of emerging technologies?